DEVELOPMENT OF ENVIRONMENTALLY FRIENDLY CRTT INTEGRATED ELECTROCHEMICAL EDUCATIONAL KITS AS LEARNING MEDIA FOR PARTNER SCHOOLS OF SMA LABS UM - Hayuni Retno Widarti; Dwi Sulistyorini; Raden Bambang Sumarsono; Istri Setyowati; Deni Ainur Rokhim; Alfina Dwi Marestya; Fasha Juliandani (UNESA Journal of Chemical Education, 2026)
This study aims to develop environmentally friendly electrochemical edukits integrated with the Culturally Responsive Transformative Teaching (CRTT) approach. This study involved 32 grade XII MIPA students at SMA Laboratorium UM with a pretest and posttest design. This study shows a significant increase in learning outcomes after using the edu-kit. The data obtained also meets parametric tests, indicating an increase in conceptual understanding of electrochemistry material. The edu-kit helps create more active, contextual learning that is closer to students' lives because they can relate electrochemistry concepts to real situations, environmental awareness, and local cultural values. Overall, the electrochemistry edukit not only improves students' cognitive understanding but also strengthens cultural relevance and sustainability values in chemistry learning.